Keragaman pertumbuhan uji keturunan jati (Tectona grandis L.F) umur 5 tahun di Ciamis, jawa Barat - Yayan Hadiyan (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2009)
In Indonesia the demand of genetically improvement seed of teak has been increasing due to the expansion of teak plantation, while the availability of high quality seed from seed orchard is very limited. A porgeny test of teak at Ciamis West Java that will be converted into a seedling seed orchard is planned to produce improved seed. The trial is laid out in Randomized Complete Block Design (RCBD), consisting of 160 families, 4 treeplots and 10 blocks. The objective of this research is to assess the growth and its variation among the families tested at 5 years old. The best tree height (12 m) was achieved by several seed sources, while the best diameter (14.6 cm) and volume increament (27.21 M3/ha/years) was from Ciamis local seed source. Family affected diameter and volume growth significantly, but not for tree height. Individual tree heriability for stem diameter was low (0.09), while that for stem volume was moderate ().10). The genetic correlation between height and diameter was strong (rg=0.84).